Biological treatment of acidic palm oil mill effluent (POME) by using soil mixed culture (SMC) - Siti Mazlifah, Ismail (2017)
Palm oil mill generates at about 50 million tons of acidic palm oil mill effluent (POME) annually. Despite of its contribution towards the economic growth, it also produces large amount of wastewater that need to be treated. The increasing interest in acidic POME treatment attract the attention of many researchers especially in biological treatment process. This study focused on biological treatment of acidic POME by using soil mixed culture (SMC). In this study SMC was acclimatized for 10 days (30°C and 150 rpm) with acidic POME and used as inoculum. There were three objectives in this study. The first objective was to characterize the acidic POME and soil. The characterization of acidic POME involves the determination of pH value, temperature, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), total solid (TS), oil and grease, and ammoniacal nitrogen. For the soil, the characterization involves the determination of pH, texture, moisture content, conductivity, nitrogen content, organic carbon content, available phosphorus and cation-exchange capacity. The second objective was to analyze factors affecting biological treatment of acidic POME. There were five factors selected for factorial analysis. The factors were reaction time, temperature, agitation speed, soil to water ratio and soil types. Design Expert software (Version 6.0) was used for the experimental design. Two-level factorial design was applied for the factorial analysis. The analysis of variance (ANOVA) proved the stability of this model with the coefficient of determination (R2) value at 0.8301 (pH treatment), 0.8239 (BOD removal) and 0.9397 (COD removal). Reaction time gave the highest contribution in pH treatment (29.84%), BOD removal (58.49%) and COD removal (38.64%). It then followed by agitation speed at 9.29% (pH treatment), 7.54% (BOD removal) and 14.90% (COD removal). The interaction effect between reaction time and agitation speed gave highest contribution which was at 17.21% (pH treatment), 16.65% (BOD removal) and 5.54% (COD removal). The third objective was to optimize the biological treatment of acidic POME. The experimental table for the optimization was constructed by using central composite design (CCD). There were two factors chosen from the factorial analysis which were reaction time and agitation speed. From the optimization, the ANOVA showed R2 value was 0.8326 (pH treatment), 0.8991 (BOD removal) and 0.8278 (COD removal). It proved that the model was fit for regression. The suggested optimum conditions that obtained during optimization were validated by using validation experiment at reaction time of 5 days and agitation speed of 150 rpm. The result that was obtained concluded that the optimum pH value (8.14), BOD removal (99.16 %) and COD removal (81.69 %), was obtained at the suggested conditions. Therefore, the applications of Design Expert software capable in obtaining the optimum conditions. Characterization was done to understanding the substrate and inoculum properties in order to improve the treatment process. The results from the screening and optimization showed that the used of SMC was a suitable for acidic POME treatment.